Adjusted cost analysis of video televisits for the care of people with amyotrophic lateral sclerosis. Issue 2 (27th June 2019) - Paganoni, Sabrina; van de Rijn, Marc; Drake, Kristin; Burke, Katherine; Doyle, Michael; Ellrodt, Amy Swartz; Nicholson, Katherine; Atassi, Nazem; de Marchi, Fabiola; Babu, Suma; Estrada, Juan; Schwamm, Lee H.; et al.
ABSTRACT: Introduction : We previously reported our amyotrophic lateral sclerosis (ALS) video televisit experience. Here we report on video televisit versus in‐clinic costs, adjusting for perceived medical usefulness (MU). Methods : We take the patient‐perspective and a focused institutional‐perspective. Costs are adjusted for patient/caregiver and physician perceptions of visit MU. The base‐case reflects our outpatient ALS practice. Results : In the base‐case, from the patient perspective, in‐clinic visits cost $1, 116 and video televisits cost $89 ($119 after MU‐adjustment). From the institutional perspective, clinic visits cost $799, and video televisits cost $354 ($472 after MU‐adjustment). Adjusted cost‐savings per televisit are $997 (patient) and $327 (institution). Sensitivity analyses on 5 variables accounted for uncertainty in base‐case assumptions. Conclusions : Video televisits provide marked adjusted cost‐savings for patients and institutions. Adjusted costs are sensitive to perceived MU of video televisits. Future research should explore the ability of video televisits to reduce healthcare resource usage. Muscle Nerve 60 : 147–154, 2019